PERAN DIPLOMASI PARLEMEN INDONESIA DALAM UPAYA MEMBANTU FIJI MENGHADAPI TANTANGAN KEAMANAN LINGKUNGAN - Rizqiah, Liza; Burhanuddin, Agussalim (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research focuses on analysing the Fiji government's policies and efforts in dealing with environmental security threats after receiving diplomacy from the Indonesian parliament. Using the desk research method, this study collected and analysed data to assess the effectiveness of Indonesian parliamentary diplomacy. The data was analysed using induction and deduction techniques, allowing general conclusions from specific data and specific conclusions from general data. Parliamentary diplomacy, as one component of multi-track diplomacy, plays an important role in post-Cold War international relations. Parliaments, including the Indonesian Parliament, play an active role in bilateral and international cooperation to advance national interests and ensure the implementation of international agreements. DPR RI demonstrates its commitment to disaster management and climate change through its participation in international forums such as the APPF and IPU. Indonesia also initiated regional cooperation through IPPP, which highlights the importance of marine resource sustainability and mitigation of climate change impacts. Fiji, as an island nation vulnerable to natural disasters and climate change, has shown a positive response to Indonesia's parliamentary diplomacy. Fiji's national policies, such as the Republic of Fiji National Climate Change Policy, reflect agreements reached in IPPP meetings, demonstrating the significant impact of parliamentary diplomacy in Fiji's environmental policies. This research concludes that Indonesia's parliamentary diplomacy has a significant influence in supporting the Fiji government's policies in dealing with environmental security threats, demonstrating the success of parliamentary diplomacy in the context of international cooperation for environmental and climate change issues.